Building cohesion in distributed telemedicine teams: findings from the Department of Veterans Affairs National Telestroke Program - Himalaya Patel; Teresa M. Damush; Edward J. Miech; Nicholas A. Rattray; Holly A. Martin; April Savoy; Laurie Plue; Jane Anderson; Sharyl Martini; Glenn D. Graham; Linda S. Williams (BMC Health Services Research, 2021)
Abstract Background As telemedicine adoption increases, so does the importance of building cohesion among physicians in telemedicine teams. For example, in acute telestroke services, stroke specialists provide rapid remote stroke assessment and treatment to patients at hospitals without stroke specialty care. In the National Telestroke Program (NTSP) of the U.S. Department of Veterans Affairs, a virtual (distributed) hub of stroke specialists throughout the country provides 24/7 consultations nationwide. We examined how these specialists adapted to distributed teamwork, and we identified cohesion-related factors in program development and support. Methods We studied the virtual hub of stroke specialists employed by the NTSP. Semi-structured, confidential interviews with stroke specialists in the virtual hub were recorded and transcribed. We explored the extent to which these specialists had developed a sense of shared identity and team cohesion, and we identified factors in this development. Using a qualitative approach with constant comparison methods, two researchers coded each interview transcript independently using a shared codebook. We used matrix displays to identify themes, with special attention to team cohesion, communication, trust, and satisfaction. Results Of 13 specialists with at least 8 months of NTSP practice, 12 completed interviews; 7 had previously practiced in telestroke programs in other healthcare systems. Interviewees reported high levels of trust and team cohesion, sometimes even more with their virtual colleagues than with co-located colleagues. Factors facilitating perceived team cohesion included a weekly case conference call, a sense of transparency in discussing challenges, engagement in NTSP development tasks, and support from the NTSP leadership. Although lack of in-person contact was associated with lower cohesion, annual in-person NTSP meetings helped mitigate this issue. Despite technical challenges in establishing a new telehealth system within existing national infrastructure, providers reported high levels of satisfaction with the NTSP. Conclusion A virtual telestroke hub can provide a sense of team cohesion among stroke specialists at a level comparable with a standard co-located practice. Engaging in transparent discussion of challenging cases, reviewing new clinical evidence, and contributing to program improvements may promote cohesion in distributed telemedicine teams.